Predictors of impaired breastfeeding initiation and maintenance in a diverse sample: what is important? - Wallwiener, Stephanie; Müller, Mitho; Marshall, Anne; Plewniok, Katharina; Wallwiener, Christian Wilhelm; Fluhr, Herbert; Feller, Sandra; Brucker, Sara Y.; Wallwiener, Markus; Reck, Corinna (Archives of gynecology and obstetrics, 2016)
This study aimed to investigate socio-demographic, medical and psychological factors that have an impact on breastfeeding.